Transcriptomic Analysis of the Spleen from Asian Seabass (Lates calcarifer) Infected with Infectious Spleen and Kidney Necrosis Virus - Hong-Yi Xin; Lim Xin Ying; Lee Ching Pei Carmen; Mookkan Prabakaran (Viruses)
Infectious spleen and kidney necrosis virus (ISKNV) is an emerging viral pathogen with an expanding host range, posing a significant threat to economically important fish species. In this study, we isolated the ISKNV strain responsible for disease outbreaks in Asian seabass (Lates calcarifer) and analyzed the transcriptomic profile of spleen tissues from experimentally infected fish. The phylogenetic analysis confirmed that the virus belongs to clade I of ISKNV. Next-generation sequencing identified differentially expressed genes, providing a comprehensive overview of the transcriptional landscape in the spleen of ISKNV-infected fish. The pathway analysis revealed complex host–virus interactions, impacting immune regulation, endocytosis, cell communication, cell cycle arrest, and programmed cell death. To further investigate these interactions, we analyzed relevant pathways in the Reactome database for Asian seabass, humans, and zebrafish, constructed a protein–protein interaction (PPI) network using STRING database, and identified hub genes using six different algorithms. This analysis revealed 69 key genes, including 41 hub genes and 28 key genes that connect different pathways or clusters within the PPI network. These findings provide new insights into the molecular mechanisms driving ISKNV infection in Asian seabass. Future research should focus on elucidating the regulatory functions of these key genes and their roles in ISKNV pathogenesis.